Analysis of the Implementation of Islamic Values and Islamic Marketing Mix Case Study at Lor Internasional Hotel Syariah Solo - Kurniawan, Dhika Amalia; Ramadhan, Rizqa Nuzul; Zarkasy, Muhammad Ridlo (INOVATOR, 2024)
This study aims to determine whether Lor Internasional sharia hotel solo applies Islamic values and Islamic marketing mix. The application of Islamic values and the Islamic marketing mix is starting to be widely applied by Muslim business people, because Muslims are starting to realize the importance of sharia-based hotels to avoid unwanted things such as murder, drugs, illicit transactions and adultery. The approach in this research uses descriptive qualitative, data collection by observation in Islamic hotels in Solo, and conducts interviews with employees, consumers, and documentation. The results showed that Lor internation- al hotel syariah solo has implemented Islamic values in the form of tauhid values, khilafah, worship, and ihsan that have been implemented. And has fulfilled the Islamic marketing mix which includes products, prices, promotions, places, people, processes and physical evidence that have been implemented, but it has not fulfilled the requirements for the application of the Islamic marketing mix at Islamic prices (prices) and Islamic promotions (promotions), because of the application of Islamic prices in Islamic hotels in Solo there are still prices that are not transparent and the implementation of Islamic promotions at Islamic hotels in Solo is still misleading. Therefore, Lor international hotel sharia solo must maintain the Islamic values that have been implemented, and improve the Islamic marketing mix that has not been implemented properly in order to survive in the long term and continue to develop.